[Girls dressed in 'Scottish costume' for 'Highland Fling' performance] - Frank Aston::::::photographer::: (1915)
Feb. 26, 1915. Girls, seated on steps and dressed in 'Scottish costume' for 'Highland Fling' performance. See Polytechnic J. 1915 for another image of same subject.